Persuasive Communication in the Covid 19 Campaign for Children - Winda Dwi Astuti Zebua; Abdul Rahman; Syifa Astasia Utari; Ali Izah Robbani (Jurnal Komunikasi, 2022)
Increasing positive cases of Covid 19 in children in Indonesia has attracted the attention of various groups, one of which is the KemenPPPA (Kementrian Pemberdayaan Perempuan dan Perlindungan Anak/ Ministry of Women's Empowerment and Child Protection. In response to this, KemenPPPA seems to be carrying out a campaign to educate children about Covid 19. Therefore, this study aims to determine the persuasif communication of the KemenPPPA in the Covid campaign in children. This study uses descriptive qualitative methods, using primary data derived from interviews and secondary data obtained from documentation and various literature studies. The data analysis techniques are; collect data, examine the data, make categorization, then test the data, and draw conclusions. The results of this study showed that KemenPPPA carried out Covid 19 campaigns and education for children in three ways, namely, making and distributing ebooks on children's stories about Covid 19, making animated videos and also creating children's forums and conducting discussions or webinars. Then the results of the study of persuasif communication indikators start from (1) audience analysis; (2) source credibility; (3) attract personal interest; (4) message clarity; (5) time and context; (6) symbols, slogans, and acronyms; (7) semantics; (8) action suggestions; and (9) content and structure, assessed to have met the criteria or elements as persuasif communication.